Glycerolysis for Lowering Free FattyAcid of Waste Cooking Oil - M. Dani Supardan; . Adisalamun; Yanti Meldasari; Yulia Annisa; . Mahlinda (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Glycerolysis can be a useful alternative for lowering free fatty acid content present in the sustainable feedstock of waste cooking oil. In the present work, the effect of reaction parameters such as molar ratio of oil to glycerol (1:1, 1:2 and 1:3), catalyst NaOH concentration (0.875, 1.3 and 1.75 %-w of oil) and mass ratio of oil to co-solvent hexane (2:1, 4:1, 8:1) have been investigated. The reaction parameters have a remarkable effect on the free fatty acid (in term of acid value) of waste cooking oil. The final acid value decreased with an increased in molar ratio of oil to glycerol from 1:1 to 1:2. A significant reduction in acid value was not observed with a further increase in molar ratio of oil to glycerol. It has been observed that the optimum catalyst concentration of 1.3% can be reduced acid value from 12.2 to 1 mg KOH/g oil in 20 min. The addition of hexane as co-solvent affected the reaction rate due to immiscibility of the oil and glycerol phases. However, a suitable amount of co-solvent must be added to achieve an optimum of acid value reduction.